Relação entre incapacidade funcional, amplitude de movimento e dor em indivíduos com e sem lombalgia - Soares, Rafael de Souza [UNESP]; Silva, José Adolfo Menezes Garcia [UNESP]; Silva, Maria Gabriela Menezes Garcia [UNESP]; Navega, Marcelo Tavella [UNESP] (My University, 2013)
Introduction: Low back pain is characterized as pain between the inferior margins of the ribs to the gluteal fold, reaching about 80% of the population throughout life. Its repercussions can affect the functionality of the subjects in their daily activities. The aim was to investigate whether a relation between symptoms of pain in the lumbar region with range of motion and functional disability. Methods: We interviewed 101 subjects with a mean age of 22.61 ± 4.06 years, these 50 participants were 51 low back pain and other complaints of back pain. OS subjects were assessed for pain by Visual Analogue Scale (VAS), mobility Lumbar Schöbber test (TS), flexibility for the Test Sit and Reach (TSA) and feature the Oswestry Disability Index (IOI). For data analysis we used GraphPad Prism 5, the significance level was set at p ≤ 0.05. Results: No significant differences were found for the comparison between the TSA of the subjects with and without pain (p = 0.25), nor to compare the performance of the TS for the subjects with and without pain (p = 0.18). Conclusion: It is concluded that in cases evaluated the range of motion has no significant link with the pain but the pain in turn directly influence the functionality of them.

Introdução: A lombalgia é caracterizada como dor entre margens inferiores dos gradis costais até as pregas glúteas, atinge cerca de 80% da população ao longo da vida. Suas repercussões podem afetar a funcionalidade dos sujeitos em suas atividades cotidianas. O objetivo foi investigar se há relação entre sintomas de dor em região lombar com amplitude de movimento e incapacidade funcional. Métodos: Foram entrevistados 101 sujeitos com idade média de 22,61±4,06 anos, destes 50 participantes não apresentavam lombalgia e os 51 demais apresentavam queixas de dor lombar. Os sujeitos foram avaliados quanto a dor pela Escala Visual Analógica (EVA), a mobilidade lombar pelo teste de Schöbber (TS), flexibilidade pelo Teste Sentar e Alcançar (TSA) e funcionalidade pelo Índice Oswestry de Incapacidade (IOI). Para análise dos dados foi utilizado o software GraphPadPrism 5, o nível de significância foi estabelecido em p≤0,05. Resultados: Não foram encontradas diferenças significativas para a comparação entre o TSA dos sujeitos com e sem dor (p= 0,25), nem para a comparação entre o desempenho no TS para os sujeitos com e sem dor (p= 0,18). Conclusão: Conclui-se então que nos casos avaliados a amplitude de movimento não tem ligação significativa com a dor, mas a dor por sua vez influenciou diretamente a funcionalidade dos mesmos.
Relationship between functional disability, range of motion and pain in individuals with and without low back pain